Amino acid profile of the gelatin extracted from the scales of catla, rohu, grass carp and their mixed type (Bangladesh Journal of Zoology, 2017)
Gelatin was extracted from the scales of catla (Catla catla), rohu (Labeo rohita), grass carp (Ctenopharyngodon idella), and their mixed type. However, amino acid of the gelatin extracted from the scales of catla and rohu was profiled. While grass carp (0.78 ± 0.03) and mixed scales (0.78 ± 0.02) yielded similar level of gelatin, rohu had the lowest recovery (0.61 ± 0.05). Scales of catla had 0.72 ± 0.06% gelatin. Of the total 14 amino acids, the highest level of glutamic acid (6.58%) was found in the gelatin extracted from the scales of catla with the lowest level of leucine (0.76%). Gelatin extracted from rohu had the highest percent of glutamic acid (6.14) with lowest percent of leucine (0.59). Of the 10 EAAs, 8 were found in the gelatin extracted from the scales of catla and rohu. While the highest per cent of lysine (4.15) was found in the gelatin extracted from the scales of rohu, the lowest per cent (0.59) was leucine. Quantification of fish scales from the fish markets of Bangladesh and extraction optimization may increase both yield and efficiency.Bangladesh J. Zool. 44(2): 185-195, 2016